Effective training procedure for a simultaneous bimanual movement task in head-fixed mice - Tezuka, Kotaro; Osaki, Hironobu; Nishimura, Kaneyasu; Terada, Shin-Ichiro; Matsuzaki, Masanori; Masamizu, Yoshito (Frontiers in Neural Circuits, 2025)
Bimanual movements consist of simultaneous and nonsimultaneous movements. The neural mechanisms of unimanual and nonsimultaneous bimanual movements have been explored in rodent studies through electrophysiological recordings and calcium imaging techniques. However, the neural bases of simultaneous bimanual movements remain poorly understood because of a lack of effective training procedures for such movements in head-fixed rodents. To address this issue, we developed a task in which mice simultaneously pull right and left levers with their forelimbs in a head-fixed condition. Here, we conducted sessions with the link plate in which both levers were mechanically linked to help mice learn the importance of simultaneous bimanual movements. These sessions with the link plate enabled the mice to maintain high success rates even during independent sessions, where the right and left levers could move independently. In these independent sessions, mice were not required to pull both levers at the same time, but rather simply to hold levers simultaneously for a specific period. The mice that experienced sessions with the link plate showed a significantly higher ratio of simultaneous (i.e., lag < 20 ms) than nonsimultaneous lever pulls. In contrast, mice without experience in sessions with the link plate showed no significant increase in simultaneous over nonsimultaneous pulls. This study demonstrates the efficacy of our new task in facilitating repetitive simultaneous forelimb movements in rodents and provides a basis for understanding the neural mechanisms underlying bimanual movements.